Do Political Competitions Stimulate the Pace of Economic Growth? Exploring the Role of Political Institutions - Samaira Batool; Mirajul Haq (Al-Qanṭara, 2024)
The study empirically investigates the effects of political competition on the pace of economic growth while accounting for the moderating role of political institutions. For this analysis, data from 66 developing countries for the period 1995–2018 is used. Given the nature of the data, the empirical analysis was carried out through a two-step system-GMM estimation method. The analysis provides two major findings. First, the rate of economic growth accelerates as political competition grows. Second, the findings shed light on the significance of political institutions in the relationship between political competition and economic growth. The conditional effect of political competition and political systems may be a hindrance to better economic performance due to factors such as political fragmentation, weak institutional structure, and heightened corruption levels in the chosen political system. However, political competition in a stable political environment is a potent driver for better economic performance in developing countries. To be more specific, if a country maintains political stability, the pace of economic growth accelerates in response to political competition.